1990
DOI: 10.1103/physrevlett.64.737
|View full text |Cite
|
Sign up to set email alerts
|

Dielectronic recombination of hydrogenlike oxygen in a heavy-ion storage ring

Abstract: State-resolved cross sections for the dielectronic recombination of hydrogenlike oxygen ions with free electrons have been measured for the first time using the electron cooling device in the heavy-ion Test Storage Ring in Heidelberg. Energies and cross sections for individual terms of the configuration 2/2/' were determined. Two-electron resonances llnl' with n > 3 contribute 90% to the total dielectronicrecombination cross section. Energies and cross sections are in reasonable agreement with available calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…Measurements of DR cross sections utilizing an electron cooler have been made for O 7+ by Kilgus et al (1990) and calculations were made by . Comparisons between the two were made, but it is easier to view the level of agreement in the figure presented by Kilgus et al (1990) rather than in the one shown by .…”
Section: O 7 +mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of DR cross sections utilizing an electron cooler have been made for O 7+ by Kilgus et al (1990) and calculations were made by . Comparisons between the two were made, but it is easier to view the level of agreement in the figure presented by Kilgus et al (1990) rather than in the one shown by .…”
Section: O 7 +mentioning
confidence: 99%
“…Comparisons between the two were made, but it is easier to view the level of agreement in the figure presented by Kilgus et al (1990) rather than in the one shown by . However, also presented a table of Kilgus et al (1992) and calculations were made in anticipation of them by .…”
Section: O 7 +mentioning
confidence: 99%
“…of Li + (Závodszky et al 1998;Saghiri et al 1999), of C 4+ (Andersen et al 1989(Andersen et al , 1990Kilgus et al 1990Kilgus et al , 1993Schuch et al 1997), O 6+ (Andersen et al 1989(Andersen et al , 1990, Ne 8+ (Zong et al 1998), Si 12+ (Kenntner et al 1995;Bartsch et al 1997), Ar 16+ (Ali et al 1990(Ali et al , 1991Dewitt et al 1991), and Ti 20+ (O'Rourke et al 2004), Fe 24+ (Beiersdorfer et al 1992), Ni 26+ and Mo…”
Section: Introductionmentioning
confidence: 99%
“…2). A detailed comparison [13,15] of the DR spectrum of O 7+ to theoretical calculations [15] shows a remarkable agreement, in particular with respect to the resonance strengths. The comparison also served to verify the degree of refinement required in the theoretical analysis [15].…”
Section: Hydrogen-like Ionsmentioning
confidence: 65%
“…For the first DR measurement [13] at the TSR, using 0 7+ ions of 8.9 MeV/amu, and for a later measurement with C s+ ions of 9.4 MeV/amu, the DR cross-section as a function of the c.m. energy is shown in Fig.…”
Section: Hydrogen-like Ionsmentioning
confidence: 99%